Enviro-toons green themes in animated cinema and television - PIke, Deidre M., 1965- (McFarland & Company, Publishers, 2012)
"This book takes an ecrocritical approach to analytical readings of animated feature films, short subjects and television shows. Beginning with the "simply subversive" environmental messages in cartoons of the 1920s to including the works of Japanese animator Hayao Miyazaki. The appendix provides a list of film and television titles honored with the Environmental Media Award for Animation"--Provided by publisher.